2010
DOI: 10.1080/09658211.2010.510476
|View full text |Cite
|
Sign up to set email alerts
|

Childhood amnesia: Empirical evidence for a two-stage phenomenon

Abstract: The term childhood amnesia refers to the inability of adults to remember events from their infancy and early childhood. If we plot the number of memories that adults can recall as a function of age during childhood, the number of memories reported increases gradually as a function of age. Typically, this finding has been used to argue that gradual changes in memory development contribute to a gradual decline in childhood amnesia during the preschool period. Alternatively, it is possible that pooling data acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 40 publications
3
47
1
Order By: Relevance
“…Finally, the finding that asking about public-event knowledge and self-relevant knowledge had a similar effect on age estimates seems to be at odds with findings that extensive cueing renders earlier memories (Jack & Hayne, 2010). However, our self-relevant questions may have been too generic to provide an advantage over a natural tendency to self-generate cues based on autobiographical knowledge.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Finally, the finding that asking about public-event knowledge and self-relevant knowledge had a similar effect on age estimates seems to be at odds with findings that extensive cueing renders earlier memories (Jack & Hayne, 2010). However, our self-relevant questions may have been too generic to provide an advantage over a natural tendency to self-generate cues based on autobiographical knowledge.…”
Section: Discussioncontrasting
confidence: 53%
“…Roughly 40% of participating children (up to 12-13 years old) recalled events from before age 2, compared to 4% of adults. Jack and Hayne (2010) found that even adults can come up with memories from under age 2 when a timeline is combined with exhaustive interviewing.…”
mentioning
confidence: 99%
“…Independent samples t-tests revealed that in animals only exposed to the context at P17, MK801 given prior to conditioning at P27 significantly reduced the level of freezing exhibited the following day compared to saline-treated animals, t 10.94 = −3.40, p = .01. 2 This demonstrates that MK801 attenuated the acquisition of context conditioning for the first time. However, there was no effect of MK801 on re-acquisition in animals previously conditioned to the context at P17, t 16 = .22, p = .83.…”
Section: Testmentioning
confidence: 92%
“…For example, most adults do not remember events that occurred before they were 4 years old [1]. This effect is known as infantile (or childhood) amnesia [2]. Importantly, this phenomenon has been demonstrated extensively across species, and is observed even when levels of learning are equated across younger and older animals [3].…”
Section: Introductionmentioning
confidence: 97%
“…Subsequent studies that were more methodologically sound have essentially agreed that adults rarely remember events from their childhood that occurred prior to the age of 3,and memories for events that occur between the ages of 3-7 are sparse [10][11][12][13]. In recent years, a number of theories have emerged that attempt to explain infantile amnesia in the context of human cognitive and social developmental milestones.…”
mentioning
confidence: 97%